2023
DOI: 10.1039/d2fo03306b
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid combined with epigallocatechin-3-gallate mitigates d-galactose-induced gut aging in mice

Abstract: CGA plus EGCG improve the gut barrier injury in aging mice induced by d-galactose through modulating the tight junctions, inflammation, oxidative stress and dysbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The reported mechanism was mediated by suppressing gut inflammation and modulating the gut microbiome, as altered by D-galactose (e.g., decreased the abundance of Lactobacillaceae, while increasing the abundance of Lachnospiraceae). 51 Alternatively, it was reported that the gut microbiota generates bioactive flavonoid metabolites, retaining anti-oxidative and anti-inflammatory properties, which could stimulate vagus nerve signals or be transported to the brain via systemic circulation, processes that are important for treating neurological disorders. 52 In the case of the application of Seabuckthorn, the intake of Seabuckthorn polysaccharide in high-fat diet-induced mice with cognitive dysfunctions reversed gut dysbiosis by correcting the reduction of Ileibacterium and increase in Lactobacillus, etc., as well as alleviating gut barrier impairment, inflammatory responses and LPS invasion in the blood circulation.…”
Section: Food and Function Papermentioning
confidence: 99%
“…The reported mechanism was mediated by suppressing gut inflammation and modulating the gut microbiome, as altered by D-galactose (e.g., decreased the abundance of Lactobacillaceae, while increasing the abundance of Lachnospiraceae). 51 Alternatively, it was reported that the gut microbiota generates bioactive flavonoid metabolites, retaining anti-oxidative and anti-inflammatory properties, which could stimulate vagus nerve signals or be transported to the brain via systemic circulation, processes that are important for treating neurological disorders. 52 In the case of the application of Seabuckthorn, the intake of Seabuckthorn polysaccharide in high-fat diet-induced mice with cognitive dysfunctions reversed gut dysbiosis by correcting the reduction of Ileibacterium and increase in Lactobacillus, etc., as well as alleviating gut barrier impairment, inflammatory responses and LPS invasion in the blood circulation.…”
Section: Food and Function Papermentioning
confidence: 99%
“…When the gut homeostasis is compromised, anti-inflammatory molecules such as SCFAs are decreased and an imbalance occurs with levels of pro-inflammatory molecules (e.g., LPS or biofilm amyloid fibres) [97,98] resulting in greater permeability of the intestinal wall, increased mitochondrial ROS production, neuronal peroxisome proliferation, as well as neurotoxin aggregation and, potentially, neurodegeneration. The decline in free radicals in the brain, through the reduction of oxidation by the modulation of the gut microbiome with the consumption of (poly)phenolic compounds, is reflected by the decrease in the level of malondialdehyde (MDA) and ROS, which is concordant with the changes in SCFAs production or the increase in SCFA-producing bacteria in several studies [74,80,82,85,[99][100][101][102][103][104][105][106] (Table 1). This interplay between gut microbiota and brain oxidative stress highlights the potential of the gut microbiome to modulate the brain redox status.…”
Section: Insight Into Associated Molecular Mechanismsmentioning
confidence: 63%
“…This is notably illustrated by an a posteriori increase in neuroinflammation, which was observed following menopause and the associated fall in oestrogen levels [109,110]. In models of (neuro)inflammatory diseases, e.g., direct administration of amyloid beta Aβ1-42 peptide [111], D-galactose [68,[80][81][82]99,104,105] or by other neurotoxins [111], oxidative stress, inflammation and mitochondrial dysfunction occur, usually in parallel to an abnormal gut ecosystem. This is of major importance as it validates the bidirectionality of the gut-brain axis, with induced neuro-disorders causing deleterious changes at the level of the microbiome.…”
Section: Insight Into Associated Molecular Mechanismsmentioning
confidence: 99%
“…Studies have shown that Lactobacillaceae could delay aging by changing the composition of the gut microbiota. 43 Lachospiraceae and Rikenellaceae could alleviate oxidative damage by clearing ROS, and Rikenellaceae could also inhibit inflammation by stimulating T cell differentiation. 44 In our study, puerarin treatment increased the abundance of Lactobacillaceae, Lachospiraceae, and Rikenellaceae, which is beneficial to alleviate oxidative stress and inflammation, thus further delaying aging.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that LPS treatment downregulated the ratio of Firmicutes/Bacteroidota , and puerarin treatment could restore the ratio of Firmicutes/Bacteroidota . Studies have shown that Lactobacillaceae could delay aging by changing the composition of the gut microbiota .…”
Section: Discussionmentioning
confidence: 99%